Factors influencing advertising in Malaysia from an Islamic perspective: case of Kedah state - Abdul Kadir, Aniss Yusairah; Al-Aidaros, Al-Hasan (IRMBR, 2015)
In many cases, business promotion costs may cause more than the cost of the product along with its research and development.Promotion through advertising is not only to introduce new products, but also to remind society of the existence of a long product in the market. However, it should be noted religion still plays a significant role in influencing social and consumer behavior either direct or indirect ways in a constantly changing and competitive world market.Goals do not justify the means and advertising cannot be as tools to increase the revenue of an organization with anything unfair. But nowadays, most of contemporary advertising makes false promises to attract new customers to buy a product which is extremely prohibited in Islam.Many of the provisions in fiqh muamalat, prohibit any method to influence the requirements of the user. Therefore this study could make important contribution in advertising industry specifically to ensure they are following Islamic principles. The objective of this study is to analyze the existence advertising through three influencing factors consist of culture, control and emotions from an Islamic perspective conducted in Malaysia, i.e. Kedah state.This study conducted using quantitative approach where structured question was designed and the data were analyzed using correlations and multiple regressions.